A Prediction of Cyclical Fluctuations in Economic Variables as a Challeng for Contemporary Economics - Lis, Piotr (Studia Oeconomica Posnaniensia, 2017)
The aim of this paper is to identify the mechanisms of cyclical fluctuations in economic variables from the perspective of contemporary economics and evaluate their predictive capabilities. The paper has stressed the substantial research achievements of contemporary mainstream economics in terms of cyclical fluctuations in economic variables. The stochastic conception of fluctuations should be the dominant recognition in contemporary mainstream economics. After the supply or demand shock, an economy returns to equilibrium - usually in an expiring way until it is interrupted by another shock. Continuous shocks make it impossible to achieve a steady state in an economy. Possibilities to identify the moment of the supply or demand shock are really limited; however the mechanism of cyclical fluctuations in economic variables is well recognized.